A manual of devotion for soldiers and sailors ... - Alexander, James W. (Presbyterian Board of Publication collection, 1847)
1. Forms of prayer, public and private -- 2. A compend of Bible truth / by Archibald Alexander -- 3. The Assembly's Shorter catechism -- 4. A selection of psalms and hymns.